Step-by-step explanation:
(a + b)² = 9
(b + c)² = 25
(a + c)² = 81
Taking the square root:
a + b = ±3
b + c = ±5
a + c = ±9
By adding these three equations together and dividing both sides by 2, we get the value of a + b + c.
Possible combinations for a + b + c such that the sum is greater than or equal to 1 are:
a + b + c = (-3 + 5 + 9)/2 = 11/2
a + b + c = (3 − 5 + 9)/2 = 7/2
a + b + c = (3 + 5 + 9)/2 = 17/2
The answer is 78
Explanation:
65 / 5 = 13
(13 = 1/6)
13*6 = 78
Answer:
a
Step-by-step explanation:
Answer:
it would be c because you add them